2011
DOI: 10.1523/jneurosci.3311-09.2011
|View full text |Cite
|
Sign up to set email alerts
|

Power Fluctuations in Beta and Gamma Frequencies in Rat Globus Pallidus: Association with Specific Phases of Slow Oscillations and Differential Modulation by Dopamine D1and D2Receptors

Abstract: Modulation of oscillatory activity through basal ganglia-cortical loops in specific frequency bands is thought to reflect specific functional states of neural networks. A specific negative correlation between beta and gamma sub-bands has been demonstrated in human basal ganglia and may be key for normal basal ganglia function. However, these studies were limited to Parkinson's disease patients. To confirm that this interaction is a feature of normal basal ganglia, we recorded local field potential (LFP) from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 57 publications
6
28
0
Order By: Relevance
“…Our findings establish that β-band oscillations in the VMS occur predominantly in brief, approximately 100-to 200-ms bursts. We found no evidence for prolonged periods of β-oscillations when we analyzed the data trial by trial, consonant with findings by Dejean et al (19). Remarkably, the β-bursts that we observed directly corresponded to transient episodes in which the spikes of striatal FSIs and projection neurons were synchronized to the β-band oscillations.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings establish that β-band oscillations in the VMS occur predominantly in brief, approximately 100-to 200-ms bursts. We found no evidence for prolonged periods of β-oscillations when we analyzed the data trial by trial, consonant with findings by Dejean et al (19). Remarkably, the β-bursts that we observed directly corresponded to transient episodes in which the spikes of striatal FSIs and projection neurons were synchronized to the β-band oscillations.…”
Section: Discussionsupporting
confidence: 92%
“…The present study observed that dopamine D 2 -like receptor antagonists, but not D 1 -like receptor antagonists, increased the power of HVS activity in the M1 cortex and LFP of the GP, indicating that D 2 -like receptors play a role in the modulation of HVSs. This is in line with previous findings which suggest that dopamine D 2 -like receptors may have a special role in the regulation of BG rhythmic activity via dopamine [29]. As the GP comprises extensive local axon collaterals, and projects to all other BG nuclei, it is considered to be central in propagating and synchronizing oscillatory activity in the cortical–BG networks [30], [31], [32].…”
Section: Discussionsupporting
confidence: 92%
“…We have previously reported that striatal LFPs show mutually exclusive dynamic states, characterized by combinations of either ~20 Hz beta and ~50 Hz low-gamma rhythms, or ~8 Hz theta and ~80 Hz high-gamma rhythms, respectively (Berke, 2009; see also Dejean et al, 2011). These distinct states were visible in our current comodulograms: in STR, GP, and STN ~50 Hz power was positively correlated with beta power and negatively correlated with ~80 Hz activity.…”
Section: Resultsmentioning
confidence: 99%